A Computational Mapping of Online News Deserts on African News Websites - Madrid-Morales, Dani (2023)
To date, the study of news deserts, geographic spaces lacking local news and information, has largely focused on countries in the Global North, particularly the United States, and has predominantly been interested in the causes and consequences of the disappearance of local media outlets (e.g., newspapers and TV stations) to the social fabric of a community. In this article, we extend the concept of “news deserts” by drawing on literature on the geography of news in Africa, where information voids have long been documented but have not been studied within the conceptual framework of news deserts. Using computational tools, we analyse a sample of 519,004 news articles published in English or French by news websites in 39 African countries. We offer evidence of the existence of online news deserts at two levels: at a continental level (i.e., some countries/regions are hardly ever covered by online media of other African countries) and at a domestic level (i.e., online news media of a given country seldom cover large areas of the said country). This article contributes to the study of news deserts by (a) examining a continent that has not been featured in previous research, (b) testing a methodological approach that employs computational tools to study news geographies online, and (c) exploring the flexibility of the term and its applicability to different media ecosystems.